Rethinking liminality in refugee and migration studies - Marotta, Vince (Ethnicities, 2025)
Drawing on anthropological theories, this paper delves into the evolving discourse on liminality within contemporary refugee and migration studies. While refugee scholars have been at the forefront in applying liminality, there has been an increasing trend in employing it to describe the immigrant experience more generally. Thus, liminality has emerged as a significant concept in understanding the migration experience, akin to established notions such as “structure” and “practice”. The paper identifies three key themes in the discourse on liminality within the refugee and migration literature: the adoption of a linear understanding of the rites of passage; a debate on whether positive or negative characteristics accurately reflect the experience of the liminal refugee/migrant subject and finally claims that the refugee and/or migration experience can be conceived as a state of permanent liminality. Through an analysis of each of these themes, I argue that existing refugee and migration scholarship oversimplifies the idea of liminality by downplaying the dialectical and relational view found in the work of anthropologists such as Arnold van Gennep and Victor Turner. By systematically reengaging with these original anthropological sources and reconsidering concepts like van Gennep’s post-liminal via the work of Clay H. Trumbull and drawing on Turner’s concept of the liminoid, the paper advocates for a more multifaceted and nuanced conceptualization of liminality that is currently missing. This rethinking of liminality can enrich our understanding and provide a deeper analysis of the ritualistic and transformative aspects of the refugee and migration experience.